"n Ekoteologiese besinning oor die Christelik-etiese implikasies van stamselnavorsing en -terapie - Hoffman, Stephan (HTS teologiese studies, 2010)
An Eco theological reflection on Christian-ethical implications of stem cell research and therapyThe new biotechnological context in which in vitro fertilisation, the human genome project, and stem cell research have become realities, confronts both society and theology with unique challenges. These realities compel us to revisit ethical questions regarding human life. The main aim of this study is to contribute to the transversal debate about Christian ethics, natural sciences and biotechnological development, from a post-foundational perspective. The research results do not aim to lay down ethical rules as absolute truths, but rather to reflect on different viewpoints, values, characteristics, virtues, moral narratives and perspectives with regard to these complex ethical dilemmas. The broadening of moral narratives, and the revaluing of relational Christiananthropological perspectives, are being presented as an alternative to the strict monolithically orientated ideas of truth, objectivity and reason.